MOLECULAR CHARACTERIZATION OF TURKISH HAZELNUT CULTIVARS AND ACCESSIONS - T. Demir (Journal of Animal and Plant Sciences, 2014)
The present study was conducted to determine the molecular profile of hazelnut cultivars and accessions grown in Turkey, and to assess their genetic relationships. Fifteen Turkish hazelnut cultivars and twelve hazelnut accessions were used as plant materials. Genetic relationships of 27 hazelnut cultivars and accessions were assessed using 22 Random Amplified Polymorphic DNA (RAPD) primers. Thirteen of the 22 primers produced polymorphic patterns resulting in 29 informative alleles. The best polymorphism was obtained from OPAD-02 (5 polymorphic bands) primer. Reproducible and clear 29 polymorphic fragments were used calculating similarity matrix and constructing dendrogram with UPGMA cluster analysis of MVSP 3.13 software. The mean number of alleles per locus was 2.23 while the similarity over the 13 polymorphic loci averaged 0.697. UPGMA cluster analysis of the data separated the 27 genotypes into two main groups. Most of the hazelnut cultivars were settled on the first group while ‘Kalınkara’, ‘İncekara’ and ‘Mincane’ cultivars and ‘FAE-190’ accession were placed on the second group. Depending on the genotypes, similarity ratios ranged from 0.364 to 0.974, with a mean value of 0.697. Overall, the results demonstrate a high level of polymorphism among hazelnut cultivars and accessions in Turkey.
Keywords: Hazelnut (Corylus); RAPD; Molecular marker; Germplasm